Effects of an Educational Comic Book on Knowledge Related to the Safe Use of Fluoride Toothpaste in Children - Henrique Cesar de Souza Perez; Luciane Zanin de Souza; Flávia Martão Flório (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To evaluate the effect of an educational comic book on indirectly supervised tooth brushing practices in early childhood education. Material and Methods: This is a quantitative action research aimed at evaluating the effect of a comic book on the necessary knowledge for indirectly supervised tooth brushing practices in early childhood education. Thirty-eight teachers from three daycare centers in the city of Porto Real, Brazil, participated in the year 2021, being carried out in three stages: 1: teachers answered a questionnaire for the identification of their sociodemographic and professional profile, in addition to prior knowledge about oral health. They also sent a photo of the toothbrush after applying the amount of toothpaste they used during the indirect supervised tooth brushing at the daycare center; 2: reception and 30 days to read the comic book; 3: answer to a new instrument on knowledge about oral health. Sending a new photo of the toothbrush with the toothpaste. Results: The amount of paste applied to toothbrushes decreased after reading the comic book from 58.1% to 27.8% of tufts, on average (p<0.05). Reading the comic allowed an increase in the frequency of respondents who acquired knowledge about the term “dental fluorosis” (p<0.05). Conclusion: Reading the comic book allowed a change in the knowledge required for the practice of indirect supervised tooth brushing.